Fullerene modification of Ag3PO4 for the visible-light-driven degradation of acid red 18. Issue 89 (9th September 2016) - Xu, Tianyuan; Zhu, Runliang; Zhu, Jianxi; Liang, Xiaoliang; Zhu, Gangqiang; Liu, Yun; Xu, Yin; He, Hongping
Abstract : Modification of Ag3 PO4, by incorporation of fullerene, could improve the photocatalytic performance and structural stability of Ag3 PO4 . Abstract : This work synthesized a C60 /Ag3 PO4 composite via the modification of Ag3 PO4, by incorporation of an acid treated fullerene (C60 ), with the aim of improving the photocatalytic activity and stability of Ag3 PO4 . XRD, SEM, Raman, XPS, PL, and UV-vis DRS were used to study the structural characteristics of the obtained photocatalysts. Acid red 18 (AR18) was adopted to evaluate the photocatalytic activity of the as-prepared photocatalysts under visible light irradiation. The results showed that C60 was successfully hybridized with Ag3 PO4, and the C60 /Ag3 PO4 composite showed higher photocatalytic activity and better stability than Ag3 PO4 . The enhancement of photocatalytic activity strongly depended on the amount of C60 on Ag3 PO4, and the optimum amount was found to be a weight ratio of 2% (C60 /Ag3 PO4 ). Superoxide radical anions (O2 ˙ − ) were confirmed to be the main participants in the degradation of AR18, determined by the active free radical capture experiments, and O2 ˙ − production by 2% C60 /Ag3 PO4 was nearly 1.5 times higher than that by Ag3 PO4 . The superior photocatalytic activity and stability of C60 /Ag3 PO4 could be attributed to the presence of C60, which can not only be used as an electron acceptor for photo-induced electrons from Ag3 PO4 to reduce the recombination of photo-induced electron–hole pairs, but also to improve O2 ˙ − production during the photocatalysis process.